Musik dan Harmoni Alam: Perspektif Filsafat IPA dan Islam - Manasikan, Oktaffi Arinna (International Journal of Science, Technology and Applications, 2023)
This research examines the relationship between music and the laws of nature through the perspective of the philosophy of science and Islamic values. Using the literature review method, various classical and contemporary texts, including the Qur'an, Hadith, and the thoughts of scholars, are analysed to understand music as a reflection of the harmony of the cosmos. Science philosophy views music as a form of mathematical and physical patterns that describe the order of the universe. On the other hand, in Islam, music is associated with dimensions of spirituality and morality, which highlight the harmony between humans and nature. This research shows that both science philosophy and Islam emphasise the importance of the relationship between art, science and spirituality in understanding the universe. The findings expand cross-disciplinary understanding of the role of music in reflecting the beauty and order of nature, and open up opportunities for further study of the impact of music on human life from a scientific and spiritual perspective.